2018
DOI: 10.1371/journal.pone.0204701
|View full text |Cite
|
Sign up to set email alerts
|

Recollection of participating in a trial: A qualitative study of patients with severe and very severe chronic obstructive pulmonary disease

Abstract: BackgroundDespite having similar palliative needs to patients with lung cancer, advanced chronic obstructive pulmonary disease (COPD) patients are less likely to receive palliative care. To evaluate the effect of introducing specialized palliative care with severe to very severe COPD patients, a randomized controlled trial (RCT) was conducted in Switzerland.AimTo explore COPD patients’ recollection of the trial, their needs and the usefulness of the palliative care interventions.Design and settingQualitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 41 publications
0
24
0
2
Order By: Relevance
“…Little information exists on existing services [ 27 ]. Here we have focused on the patients’ needs and perceptions to provide insights into the most adequate interventions [ 28 ]. The results of this study, in addition to further investigations about perceptions of care providers, social workers, volunteers and municipal authorities, will serve as the basis for developing acceptable, feasible and sustainable solutions, involving all stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Little information exists on existing services [ 27 ]. Here we have focused on the patients’ needs and perceptions to provide insights into the most adequate interventions [ 28 ]. The results of this study, in addition to further investigations about perceptions of care providers, social workers, volunteers and municipal authorities, will serve as the basis for developing acceptable, feasible and sustainable solutions, involving all stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies brought a basic taxonomy of palliative care in advanced COPD [27]. Still, some unresolved issues remain and need to be addressed if palliative care is to be standardised and widely recommended [7,15,19]. The early introduction of palliative care is under investigation, as studies so far identified existing barriers, but not necessarily particular benefits for patients [18].…”
Section: Resultsmentioning
confidence: 99%
“…Participants in the intervention group admitted, however, a lessened impact of COPD symptoms and a more positive attitude towards advanced care planning at some point during the intervention [19]. Importantly, recollection of participating in an early palliative care intervention for severe and very severe COPD patients was poor [7]. In turn, an intervention that was highly valued by patients suffering from breathlessness was based on integrative respiratory and palliative care that assured active symptom management, individualised education and advanced care planning [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations